Application of mixed starter culture for table olive production - Z.Ş. Erdemir Tıraş; H. Kalkan Yıldırım (Grasas y Aceites, 2021)
The fermentation of olives is usually carried out spontaneously by natural microbiota. Spontaneous fermentation has some disadvantages, such as the formation of defects in the end product due to the activities of undesirable microorganisms. The use of starter cultures could be a promising option to provide a more controlled fermentation environment and to reduce the risk of spoilage. Mixed starter culture use (generally selected Lactobacillus strains with or without yeasts) could reduce pH in a shorter time, producing a higher amount of lactic acid and enhancing microbial safety compared to fermentation with starter cultures containing single species or natural fermentation. Their use could also enhance the organoleptical properties of table olives. Particularly the use of yeast (such as strains of W. anomolus, S. cerevisiae) in the fermentation of olives, in combination or sequentially with lactic acid bacteria could result in an increase in volatile compounds and a more aromatic final product.